Ukraine : 2002 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Ukraine. (IMF Staff Country Reports; Country Report, 2002)
This 2002 Article IV Consultation highlights that the economic situation in Ukraine has continued to improve in 2001. Real GDP growth is estimated to have increased from almost 6 percent in 2000 to 9 percent in 2001, mainly on account of double-digit growth of industrial output and a good grain harvest, resulting from favorable weather conditions and a lessening of government controls in agriculture. Fiscal policy through end-September 2001 was broadly on track, although indicators of revenue were affected by the accumulation of arrears on value-added tax refunds.